Biomarker‐driven prognostic models in chronic heart failure with preserved ejection fraction: the EMPEROR–Preserved trial. (24th July 2022) - Pocock, Stuart J.; Ferreira, João Pedro; Packer, Milton; Zannad, Faiez; Filippatos, Gerasimos; Kondo, Toru; McMurray, John J.V.; Solomon, Scott D.; Januzzi, James L.; Iwata, Tomoko; Salsali, Afshin; Butler, Javed; et al.
ABSTRACT: Aims: Biomarker‐driven prognostic models incorporating N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and high‐sensitivity cardiac troponin T (hs‐cTnT) in heart failure (HF) with preserved ejection fraction (HFpEF) are lacking. We aimed to generate a biomarker‐driven prognostic tool for patients with chronic HFpEF enrolled in EMPEROR‐Preserved. Methods and results: Multivariable Cox regression models were created for (i) the primary composite outcome of HF hospitalization or cardiovascular death, (ii) all‐cause death, (iii) cardiovascular death, and (iv) HF hospitalization. PARAGON‐HF was used as a validation cohort. NT‐proBNP and hs‐cTnT were the dominant predictors of the primary outcome, and in addition, a shorter time since last hospitalization, New York Heart Association (NYHA) class III or IV, history of chronic obstructive pulmonary disease (COPD), insulin‐treated diabetes, low haemoglobin, and a longer time since HF diagnosis were key predictors (eight variables, all p < 0.001). The consequent primary outcome risk score discriminated well ( c ‐statistic = 0.75) with patients in the top 10th of risk having an event rate >22× higher than those in the bottom 10th. A model for HF hospitalization alone had even better discrimination ( c = 0.79). Empagliflozin reduced the risk of cardiovascular death or hospitalization for HF in patients across all risk levels. NT‐proBNP and hs‐cTnT were also the dominant predictors of all‐cause and cardiovascular mortality followed by history of COPD, low albumin, older age, left ventricular ejection fraction ≥50%, NYHA class III or IV and insulin‐treated diabetes (eight variables, all p < 0.001). The mortality risk model had similar discrimination for all‐cause and cardiovascular mortality ( c ‐statistic = 0.72 for both). External validation provided c ‐statistics of 0.71, 0.71, 0.72, and 0.72 for the primary outcome, HF hospitalization alone, all‐cause death, and cardiovascular death, respectively. Conclusions: The combination of NT‐proBNP and hs‐cTnT along with a few readily available clinical variables provides effective risk discrimination both for morbidity and mortality in patients with HFpEF. A predictive tool‐kit facilitates the ready implementation of these risk models in routine clinical practice. Abstract : Biomarker‐driven prognostic models for heart failure (HF) with preserved ejection fraction. COPD, chronic obstructive pulmonary disease; hs‐cTn, high‐sensitivity cardiac troponin T; LVEF, left ventricular ejection fraction; NT‐proBNP, N‐terminal pro‐B‐type natriuretic peptide; NYHA, New York Heart Association.